Erythrocyte membrane-camouflaged carrier-free nanoassembly of FRET photosensitizer pairs with high therapeutic efficiency and high security for programmed cancer synergistic phototherapy - Xuanbo Zhang; Jianchen Xiong; Kaiyuan Wang; Han Yu; Bingjun Sun; Hao Ye; Zhiqiang Zhao; Ning Wang; Yuequan Wang; Shenwu Zhang; Wutong Zhao; Haotian Zhang; et al. (Bioactive Materials, 2021)
Phototherapy has been intensively investigated as a non-invasive cancer treatment option. However, its clinical translation is still impeded by unsatisfactory therapeutic efficacy and severe phototoxicity. To achieve high therapeutic efficiency and high security, a nanoassembly of Forster Resonance Energy Transfer (FRET) photosensitizer pairs is developed on basis of dual-mode photosensitizer co-loading and photocaging strategy. For proof-of-concept, an erythrocyte-camouflaged FRET pair co-assembly of chlorine e6 (Ce6, FRET donor) and 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindotricarbocyanine iodide (DiR, FRET acceptor) is investigated for breast cancer treatment. Notably, Ce6 in the nanoassemby is quenched by DiR and could be unlocked for photodynamic therapy (PDT) only when DiR is photobleached by 808-nm laser. As a result, Ce6-caused phototoxicity could be well controlled. Under cascaded laser irradiation (808–660 nm), tumor-localizing temperature rise following laser irradiation on DiR not only induces tumor cell apoptosis but also facilitates the tumor penetration of NPs, relieves tumor hypoxia, and promotes the PDT efficacy of Ce6. Such FRET pair-based nanoassembly provides a new strategy for developing multimodal phototherapy nanomedicines with high efficiency and good security.